NEUROSURGICAL TECHNOLOGIES IN MENTAL HEALTH CARE: SOCIETAL, WELL-BEING, AND PUBLIC POLICY IMPLICATIONS - Justyna Karliczek; Natalia Kitala; Julia Knap; Jędrzej Sztajura (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and purpose: Neurosurgery, traditionally focused on life-saving and functional preservation, also profoundly impacts mental integrity due to its direct interaction with the brain. Psychiatric neurosurgery, including deep brain stimulation and advanced stereotactic techniques, actively modulates dysfunctional neural circuits in treatment-resistant psychiatric disorders. This review examines how such interventions influence personality, cognition, and social functioning, highlighting their evolving role as evidence-based therapeutic options that extend beyond conventional clinical outcomes. Materials and methods: The literature search was performed using PubMed, Scopus, Web of Science, and Google Scholar. Keywords included: “psychiatric neurosurgery”, “deep brain stimulation”, “DBS”, “vagus nerve stimulation”, “VNS”, “auricular vagus nerve stimulation”, “aVNS”, “stereotactic neurosurgery”, “treatment-resistant depression”, “major depressive disorder”, “obsessive-compulsive disorder”, “OCD”, “treatment-resistant psychiatric disorders”, “personality changes”, “cognitive changes”, “neuropsychiatric outcomes”, “quality of life”, “social functioning”, “employment”, “cost-effectiveness”, and “caregiver burden”. Conclusion: Psychiatric neurosurgery, including deep brain stimulation and vagus nerve stimulation, demonstrates significant clinical and socioeconomic benefits for patients with treatment-resistant psychiatric disorders. Beyond symptom reduction, these interventions can restore cognitive and emotional functioning, enhance quality of life, improve social integration, and facilitate professional reintegration. Additionally, they alleviate caregiver burden and may reduce long-term healthcare costs. While current evidence supports the safety and efficacy of these approaches, optimal targeting strategies, patient selection, and long-term outcomes require further research. Overall, psychiatric neurosurgery represents a transformative therapeutic option, bridging clinical treatment with broader psychosocial and economic impact.